1977
DOI: 10.1007/bf00427118
|View full text |Cite
|
Sign up to set email alerts
|

A histochemical study of bone marrow hypoplasia in anorexia nervosa

Abstract: The bone marrow in patients with anorexia nervosa is commonly hypoplastic with transformation of marrow fat. The normal fat cells which appear clear and open in the marrow are surrounded by an amorphous, gelatinous material, thought to represent an increase in the ordinary acid mucopolysaccharide ground substance of the bone marrow. Since this lesion has a similar appearance grossly and microscopically to the lesion of serous fat atrophy found in cachectic patients, we have compared the histochemical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…Histological findings are atrophic adipocytes, marrow hypoplasia, and deposition of acid mucopolysaccarides, which are visible on HE stainings as an amorphous ground substance that stains positive by Alcian blue. 2,8 Based on this, the observed AFM likely represents serous fat atrophy, although no macroscopic findings were observed during necropsy. Serous fat atrophy is seen in many different conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Histological findings are atrophic adipocytes, marrow hypoplasia, and deposition of acid mucopolysaccarides, which are visible on HE stainings as an amorphous ground substance that stains positive by Alcian blue. 2,8 Based on this, the observed AFM likely represents serous fat atrophy, although no macroscopic findings were observed during necropsy. Serous fat atrophy is seen in many different conditions.…”
Section: Discussionmentioning
confidence: 93%
“…In AN, there is a reduction in normal hematopoietic tissue and increase in fat fraction, size, and number of adipocytes in the bone marrow, but the pathophysiology behind the gelatinous bone marrow transformation is unclear [13] . A large retrospective study looked at 80,000 bone marrows and found 155 cases of gelatinous bone marrow transformation (GMT) (fat cell atrophy, focal loss hematopoietic cells, deposition of extracellular gelatinous substances).…”
Section: Discussionmentioning
confidence: 99%
“…The marrow gelatinous transformation has been referred to as starvation marrow. Most of the cases of severe nutritional deficiency were seen with anorexia nervosa [1,3,5]. A depletion of protein or fat appears to account for many of the reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatinous transformation has been reported to occur in a variety of chronic disorders, including prolonged starvation, anorexia nervosa, malabsorption, malignant disease, and HIV infection [1,2]. The gelatinous substances deposited in the marrow had been demonstrated histochemically as hyaluronic acid mucopolysaccharides [3,4]. However, the pathogenic mechanism of the marrow lesion remains unclear.…”
Section: Introductionmentioning
confidence: 99%